2017
DOI: 10.1002/elan.201600764
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Photoelectrochemical Glucose Biosensor in Flow Injection Analysis System Using ZnS/CdS‐Carbon Nanotube Nanocomposite Electrode

Abstract: In this work, a photoamperometric glucose biosensor based on glucose oxidase (GODx) was developed in flow injection analysis (FIA) system using ZnS‐CdS quantum dot (QD) modified multiwalled carbon nanotube/glassy carbon electrode (ZnS‐CdS/MWCNT/GCE). Cyclic voltammograms of the proposed electrode (GODx/ZnS‐CdS/MWCNT/GCE) showed a pair of well‐defined reversible redox peak attributing that direct electron transfer between the protein and electrode. The current of the reduction peak became more cathodic in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A previously published procedure was used to functionalize MWCNTs [34]. For this aim, 1.0 g of MWCNTs were functionalized by sonicating in a solution containing 10 mL of concentrated HNO 3 and H 2 SO 4 with a ratio of v/ v 1 : 3 for 1 h at room temperature and followed by extensive washing with ultra-pure water until the pH of the filtrate reaches neutral.…”
Section: Functionalization Of Mwcntsmentioning
confidence: 99%
“…A previously published procedure was used to functionalize MWCNTs [34]. For this aim, 1.0 g of MWCNTs were functionalized by sonicating in a solution containing 10 mL of concentrated HNO 3 and H 2 SO 4 with a ratio of v/ v 1 : 3 for 1 h at room temperature and followed by extensive washing with ultra-pure water until the pH of the filtrate reaches neutral.…”
Section: Functionalization Of Mwcntsmentioning
confidence: 99%
“…Hybrid composites based on CNTs with inorganic (Tak et al, 2016;Guzsvány et al, 2017;Kaçar et al, 2017;Narang et al, 2017;Sağlam & Dilgin, 2017;Shiravand & Azadbakht, 2017;Shoja et al, 2017;Song et al, 2017), conducting polymer (Li & Lee 2015;Meiyazhagan et al, 2015;Meshram, 2015;Shrivastava et al, 2016;Ates et al, 2017;Jasim et al, 2017;Satyanarayana et al, 2017;Su et al, 2017;Vinay et al, 2017;Gui et al, 2018) and organic materials (Pereira et al, 2015;Rather et al, 2015;Thirumalraj et al, 2015;Vilian et al, 2015;Hien et al, 2017;Poo-Arporn, Pakapongpan et al 2017;Savalia & Chatterjee 2017;Thapa et al, 2017) have been reported in the recent times. Hybridisation of nanometals to carbon nanomaterials such as CNTs produces a synergistic effect on the electrocatalytic activity when compared to either material alone.…”
Section: Carbon Nanotube Nano Compositesmentioning
confidence: 99%
“…These hybrid materials formed have shown great potential application in catalysis (Baghayeri & Veisi 2015), electronics (Cavallini et al, 2015), optics and sensors (Barsan et al, 2015;Cernat et al, 2015, Zhao et al, 2015Adhikari et al, 2017;Correa et al, 2017). CNT-inorganic nanocomposites (Braga et al, 2015;Cui et al, 2015;Narang et al, 2017;Sağlam & Dilgin 2017) have opened up an exciting new field in the science and technology of CNT. CNT-metal nanoparticles have excellent conductivity and catalytic properties, which make them suitable for acting as 'electronic wires' to enhance the electron transfer between the redox centres in proteins and electrode surfaces, and as catalysts to increase electrochemical reaction rates Zhao et al, 2015;Dagar & Pundir 2017;Dalkıran et al, 2017).…”
Section: Carbon Nanotube Nano Compositesmentioning
confidence: 99%
“…However, photo-generated electrons from ZnS tend to recombine with holes, which results in an obvious decrease in the separation and transfer of photoelectrons. To overcome the problem, it is a good way to combine ZnS nanostructures with different semiconductors and carbon materials [ 4 , 5 , 6 , 7 , 8 ]. Pal et al investigated the photocurrent generation and photocatalytic activity of one-pot solvothermally-synthesized reduced graphene oxide (RGO)-ZnS composites [ 9 ].…”
Section: Introductionmentioning
confidence: 99%